Manajemen Pembelajaran Seni Rupa Berbasis Kearifan Lokal dalam Mata Pelajaran Seni Budaya Kelas VII di MTsN 1 Lombok Barat - Mi’rajus Subyan Rahmat; Pyo Apriliana Munawarah; Adawiah Rizqi Johari (Universitas Muhammadiyah Mataram, 2023)
In this study the aims to find out how the implementation of art and cultural learning activities was implemented by teachers in increasing students' creativity and knowledge starting from the planning, implementation and evaluation stages as well as supporting and inhibiting factors in the implementation of local wisdom-based art materials in class VII art and culture subjects at MTsN 1 West Lombok. Data collection techniques were carried out by interviews, observation, and documentation studies. The results of this study indicate that: (1) Cultural arts learning planning is poured into teacher learning tools but still needs to be further developed with reference to local wisdom. In visual art material, the teacher maps learning concepts that focus on two-dimensional works, namely drawing flora, fauna and natural objects as well as drawing decorations with reference to traditional regional motifs. (2) The implementation of fine arts materials is directed so that students are able to appreciate and create fine arts, learning activities are not only focused in the classroom. (3) Evaluation of fine arts material is carried out by the teacher in writing and from the two-dimensional works made by students to find out how far students' understanding of the material has increased. (4) Supporting factors are influenced by high student enthusiasm, mastery and method of delivering material interesting by the teacher and the atmosphere of a beautiful and comfortable school environment. The inhibiting factors are that not all students have tools and materials to support practical activities, lack of references to traditional motifs, lack of guidance to teachers in designing and developing lesson plans that refer to local wisdom.